Efficacy and Safety of Boldine Combined with Phyllanthus niruri and Ononis spinosa in Medical Expulsive Therapy for Distal Ureteral Stones with Renal Colic: A Single-Center, Retrospective Cohort Study - Ernesto Di Mauro; Pietro Saldutto; Roberto La Rocca; Giuseppe Sangiorgi; Gianluigi Patelli; Biagio Barone; Vittore Verratti; Roberto Castellucci; Luigi Napolitano; Fabrizio Iacono; Vincenzo Maria Altieri (Medicina)
Background and Objectives: This study aimed to compare the effects and safety of boldine combined with Phyllanthus niruri and Ononis spinosa plus tamsulosin vs. tamsulosin alone in medical expulsive therapy (MET) for distal ureteral calculi. Materials and Methods: This retrospective cohort study was conducted on 159 renal colic patients with distal ureteric stones (≤10 mm). Patients aged between 18 and 70 years or older with distal ureteral (below the sacroiliac joint) stones ≤10 mm (defined by the largest diameter in three planes) confirmed by urinary ultrasonography and/or native computed tomography (CT). Patients were divided into two groups: A and B. Patients in Group A received tamsulosin 0.4 mg plus boldine combined with Phyllanthus niruri and Ononis spinosa, while those in Group B received tamsulosin 0.4 mg. The rate of stone expulsion, duration of stone expulsion, the dose and the duration of nonsteroidal anti-inflammatory drugs (NSAIDs), analgesic use, and adverse effects of drugs were recorded. Results: No differences were reported in demographic profiles between the two groups. The stone expulsion rate in Group A (84.8%) was higher in comparison to Group B (52.5%); the mean time of stone expulsion was 16.33 ± 4.75 days in Group A and 19.33 ± 6.42 days in Group B. The mean requirement time of analgesia was significantly less in Group A, 2.42 ± 2.56, than in Group B, 6.25 ± 3.05. Drug-related adverse effects (headache, dizziness, nausea, vomiting, postural hypotension, backache, and running nose) were comparable between the two groups. Conclusions: Tamsulosin plus boldine combined with Phyllanthus niruri and Ononis spinosa as medical expulsion therapy is more effective for distal ureteric stones with less need for analgesics and a shorter stone expulsion time than tamsulosin alone.